(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Relationship between Environmental Knowledge and Green Attitudes on Purchasing Behavior in DKI Jakarta Province’s Green Stores. Currently, environmental issues have shown some negative impacts on the environment, living things, and global social and economic systems that tend to be unstable. One of the factors is a less eco-friendly lifestyle. The commitment to deal with it is to encourage our societies to prioritize consuming green products. This study aims to identify the level of environmental knowledge and the condition of green attitudes and to analyze each of those variables that relate to the green purchase intention of Jakarta’s citizens. Incidental and purposive sampling techniques were used with 80 respondents in DKI Jakarta Province. To assess the level of environmental knowledge and green attitudes, this research used an interval scale from the score of 1 to 5. The result indicates that the respondent’s environmental knowledge was very high and their green attitudes were classified in the "agree" category. Partial Least Square-Structural Equation Modelling (PLS-SEM) was used as the analysis technique for this research. That technique was showing that the positive and significant relationship means higher environmental knowledge and green attitudes, so the purchase intentions in Jakarta’s green stores will be high. The recommendation of this study is for Jakarta’s government, NGOs, and green business actors to increase the socialization of related information on environmental issues, which could encourage Jakarta’s citizens shift to prioritizing green product consumption.